A light-guiding urinary catheter for the inhibition of Proteus mirabilis biofilm formation - Butement, Jonathan T.; Noel, Daniel J.; Bryant, Catherine A.; Wilks, Sandra A.; Eason, Robert W. (Frontiers in Microbiology, 2022)
Catheter-associated urinary tract infection (CAUTI) is a leading cause of hospital-acquired infections worldwide causing debilitating illness for patients as well as a significant financial and treatment burden on health services. CAUTI is linked with the build-up of biofilms on catheter surfaces which act as a reservoir for infection. Additionally, urease-producing bacteria such as Gram-negative Proteus mirabilis (PM), can form crystalline biofilms which encrust catheter surfaces ultimately leading to blockages which require immediate removal of the catheter. Currently there are limited treatments available to prevent the formation of biofilms by PM as well as other urinary tract infection causing bacteria. A novel concept for a light-guiding urinary catheter is presented where a silicone elastomer waveguide incorporated along the length of the catheter is used to irradiate the catheter surfaces with antimicrobial blue light (405 nm) to prevent biofilm formation in-situ. The prototype device is mass producible while also easy to fabricate in a lab setting for research studies. The inhibitory effect of blue light on PM biofilm formation over a range of irradiances is described for the first time showing an LD90 at 192-345 J/cm2and total inhibition at 1700 J/cm2 In vitro studies show that the light-guiding catheter prototypes exhibit a 98% inhibition in PM biofilm formation inside the catheter lumen at an average estimated irradiance of 30 - 50 mW/ cm2 (324-540 J/cm2 fluence) showing that the concept is highly effective, promising to be a powerful and economical antimicrobial approach to prevent catheter associated biofilm development and blockage.